Função de oferta de amendoim no estado de São Paulo - Brandt, Sérgio Alberto; Dias Teixeira, Teotônio; Fagundes de Sousa, Antônio; Aad Neto, Alexandre; T Morimoto, Paulo (Revista Ceres, 2025)
The objectives of the present study were: a) to estimate the supply of peanuts in the short and long run, in the state of Sao Paulo; b) identify some of the most important variables that affect the supply of peanuts in the state of São Paulo; c) estimate the short and long run elasticities of these variables; and d) estimate the coeficient of adjustment of production.